IMPLEMENTASI MODEL PBL BERBANTUAN MEDIA DIORAMA DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF DAN KEAKTIFAN SISWA PADA PEMBELAJARAN IPAS - Ghanesa Rizal Monacco; Reyta Tri Ayuningtyas; Ani Nur Sholihah; Melik Budiarti (Universitas Tribhuwana Tunggadewi, 2026)
IPAS instruction in elementary schools still faces challenges because it is teacher-centered and does not make sufficient use of contextual media. This research is important even though the Problem-Based Learning (PBL) model has been widely applied in IPAS instruction; the use of environmental dioramas as a tool to support contextual learning in elementary schools has not yet been extensively studied. Therefore, this study is expected to provide evidence regarding the effectiveness of integrating the PBL model with environmental dioramas to improve learning outcomes and student engagement. This study aims to improve IPAS learning outcomes among fourth-grade students at SD Negeri 02 Manisrejo by using the “Problem-Based Learning” (PBL) model as a support. This is the case even though the PBL model has been widely used. This Classroom Action Research (PTK) was conducted in two cycles: planning, implementation, observation, and reflection. There were 15 students who served as research subjects. After data were collected through observation, tests, interviews, and documentation, a qualitative descriptive analysis was performed. The results of the study showed that learning outcomes improved during each cycle. Students’ average scores increased from 59.13, with a 20 percent mastery rate in the pre-cycle, to 66.6, with a 60 percent mastery rate in the first cycle, and to 89.3, with a 100 percent mastery rate in the second cycle. In addition, the use of PBL with the aid of environmental dioramas increased student participation, cooperation, and their confidence in expressing their opinions. Therefore, this model improved IPAS learning outcomes and created a more contextual and relevant learning experience.